2001
DOI: 10.1159/000054208
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic Effects of Captopril and Doxazosin during Slight Physical Activity in Hypertensive Patients with Type-1 Diabetes mellitus

Abstract: Angiotensin-converting enzyme inhibitors are renoprotective in diabetes mellitus through their intrarenal hemodynamic effects. Alpha-1 blockade has variable pre- and postglomerular vasodilatory effects dependent upon the stimulation of the sympathetic nervous system. We tested the hypothesis that the two different classes of drugs have similar renal hemodynamic effects when the patients are examined in an upright position where the sympathetic nervous system is activated. Mean blood pressure (MAP), glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…It was reported that GFR could be preserved in association with the reduction of urinary microalbumin by antihypertensive treatment [20], even with doxazosin [21]. However, several papers have demonstrated that urinary microalbumin was reduced despite the decrease in GFR in response to antihypertensive treatments [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that GFR could be preserved in association with the reduction of urinary microalbumin by antihypertensive treatment [20], even with doxazosin [21]. However, several papers have demonstrated that urinary microalbumin was reduced despite the decrease in GFR in response to antihypertensive treatments [22, 23].…”
Section: Introductionmentioning
confidence: 99%